Informational support of event manager in the project of organization of sports actions - Malyeyeva, O. V.; Glushko, I. V.; Artiukh, R. V.; Plyasheshnik, A. M. (Національний технічний університет "Харківський політехнічний інститут", 2020)
The subject of the study is the processes of information support of organizational projects. The aim of the work is to create an integrated web service for information support of event-manager in the projects of organization of sports competitions. The following tasks are solved in the article: analysis of means of information support of organizational projects, systematization of event-manager functions and means for their fulfillment, development of a web-resource for providing information support of the project of organization of sports competitions. The following methods are used: project management, communication management, queuing theory, integration of information systems, object-oriented programming. The results obtained: An analysis of the means of information support of organizational projects is carried out. It is concluded that the integration of web applications, mapping services and integration tools with social networks is necessary for effective management of organizational projects. Features and software of event-manager of projects of the organization of sports competitions which are systematized according to the main stages of the life cycle were studied. A diagram of use cases has been developed, which is the initial conceptual presentation of the information support system. A web-based user interface has been designed to create and edit online contest routes using a mapping service. The opportunity to integrate the event into the social network Facebook with editing posts was realized. The application of queuing theory methods is justified for managing the organizational risks of the project. Conclusions: Integration of modern technologies provides informational support to the event manager of the project of organization of sports competitions, which provides convenience and shortening of terms of performance of its functions. In addition, the developed web resource allows different types of project stakeholders to participate in polls, register for competitions, view reports from previous events and get directions for competitions directly on the site.

Предметом дослідження в статті є процеси інформаційного забезпечення організаційних проектів. Метою роботи є створення інтегрованого веб-сервісу для інформаційної підтримки event-менеджера в проектах організації спортивних змагань. В статті вирішуються наступні завдання: аналіз засобів інформаційного забезпечення організаційних проектів, систематизація функцій event-менеджера та засобів для їх виконання, розробка веб-ресурсу для забезпечення інформаційної підтримки проекту організації спортивних змагань. Застоствуються методи: проектного менеджменту, управління комунікаціями, теорії масового обслуговування, інтеграції інформаційних систем, об’єктно-орієнтованого програмування. Отримано результати: Проведено аналіз засобів інформаційного забезпечення організаційних проектів. Зроблено висновок про необхідність інтеграції веб-додатків, картографічних сервісів та засобів інтеграції з соцмережами для ефективного управління організаційними проектами. Розглянуто функції та програмні засоби event-менеджера проектів організації спортивних змагань, які систематизовано за основними етапами життєвого циклу. Розроблено діаграму варіантів використання, що є вихідним концептуальним поданням системи інформаційної підтримки. Спроектовано інтерфейс користувача веб-ресурсу з можливістю створення та онлайн-редагування маршрутів змагань за допомогою картографічного сервісу. Реалізована можливість інтеграції заходу у соціальну мережу Фейсбук з редагуванням постів. Для управління організаційними ризиками проекту обґрунтовано застосування методів теорії масового обслуговування. Висновки: Інтеграція сучасних технологій забезпечує інформаційну підтримку event-менеджера проекту організації спортивних змагань, що забезпечує зручність та скорочення термінів виконання його функцій. Крім того розроблений веб-ресурс дозволяє різним типам стейкхолдерів проекту брати участь у опитуваннях, реєструватися на змаганнях, дивитись звіти з попередніх подій та прокладати маршрути для змагань безпосередньо на сайті.
Використання методів статистичного аналізу при обробці даних опитування населення
Keywords: event-manager; web resource; mapping API; competition organization; integration; event-менеджери; веб-ресурси; картографічні API; організація змагань; інтеграція